Determination of the fracture parameters of the Double-K model using weight functions of split-tension specimens - Ince, Ragip (Pergamon-Elsevier Science Ltd, 2012)
Splitting tests on cubical, cylindrical and diagonal cubic concrete samples were analyzed to determine the fracture parameters for the Double-K model. Using the boundary element method, the stress intensity factors of splitting specimens subjected to four equal point loads on the notch was first derived. Subsequently, the universal four-term weight functions of these specimens were determined. To investigate how well the splitting tests were simulated by the Double-K model, the results of the splitting tests were compared with the results of beam tests using data found in the literature. It was observed that the results for the splitting specimens were more uniform than those for beams. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Concrete; Splitting test; Double-K model; Weight function; Boundary element method